Imaging-based spectrometer-less optofluidic biosensors based on dielectric metasurfaces for detecting extracellular vesicles - Yasaman Jahani (Nature Portfolio, 2021)
The authors engineer a type of bound states in the continuum in diatomic dielectric metasurfaces, allowing for high-quality resonances with accessible enhanced fields. Metasurface microarrays are integrated with microfluidics on an imaging platform for real-time detection of biosamples, based on reconstructing spectral shift information.